Infrastructure Development Inequality: When Big Projects Sacrifice Local Acess - Loso judijanto; Suharto Suharto; Kukuh Lukiyanto; Helmi Ali; Wahyu Sri Atutik; Maria Yosefina Meinadia Sekar Kinanti Aswirawan (PT. Hafasy Dwi Nawasena, 2025)
Major infrastructure development in developing countries often focuses on improving national connectivity and economic growth, but often ignores the social impact on local communities. Projects such as expressways or railway lines can break vital links between regions and increase accessibility inequalities, hinder mobility and exacerbate socio-economic inequalities. In addition, land acquisition for large projects often harms farmers and micro entrepreneurs who lose their livelihoods without adequate employment solutions. These projects also ignore local needs, such as access to essential public facilities. This inequality is exacerbated by a lack of inclusive planning, where local communities are not involved in the decision-making process. As a result, although large infrastructure development can improve the macroeconomy, its positive impact is not felt by society at the micro level. This study uses a qualitative approach with case studies to explore the impact of infrastructure development on local community access. Through interviews, field observations, and document analysis, this study aims to provide an in-depth picture of social inequalities that arise due to the dominance of large projects without considering the interests of local communities. More inclusive planning and community participation are needed to ensure sustainable and equitable development.